The Norwegian shareholder tax reconsidered - Jan Södersten; Tobias Lindhe (Uppsala University, Department of Economics, 2011)
In an article in International Tax and Public Finance, Peter Birch Sørensen (2005) gives an in-depth account of the new Norwegian Shareholder Tax, which allows the shareholders a deduction for an imputed risk-free rate of return. Sørensen's positive evaluation appears as reasonable for a closed economy where the deduction for the imputed return is capitalized into the market prices of corporate shares. We show that in a small open economy where no capitalization occurs, the Norwegian shareholder tax is likely to leave the distortions caused by the corporate income tax unaffected, and to add new distortions to shareholders' portfolio decisions.
urn:nbn:se:uu:diva-152570
Keywords: H24; H25; 330; tax neutrality; open economy; shareholder taxation; corporate-personal tax integration; small firms; Kapitalertragsteuer; Dividende; Steuerinzidenz; Kleine offene Volkswirtschaft; Theorie; Norwegen